Theoretical study of the interplay of spin density wave and superconductivity in nickel substitution of the strontium–iron–arsenide (SrFe2−xNixAs2) superconductor in a two-band model - Bogale, Gedefaw Mebratie; Shiferaw, Dagne Atnafu (Frontiers in Physics, 2023)
The main objective of this manuscript is to focus on the computational study of the interplay of spin density wave (SDW) and superconductivity using a two-band model for SrF e 2−x N i x As 2 . We derived mathematical statements for the superconducting critical temperature, the SDW critical temperature, the superconductivity order parameter, and the SDW order parameter using the Hamiltonian model and Green's function formalism for the SrF e 2−x N i x As 2 superconductor. A mathematical expression for the dependence of transition temperatures on the SDW order parameter was obtained for SrF e 2−x N i x As 2 . Using these mathematical statements, transition temperatures versus the SDW order parameter phase diagrams were plotted to show the dependence of the SDW order parameter on transition temperatures. By merging these diagrams, we have depicted the intriguing possibility of the interplay of superconductivity and magnetism for the SrF e 2−x N i x As 2 superconductor. Phase diagrams of temperature versus superconducting order parameters and SDW order parameter were also plotted to show the dependence of order parameters on temperature for the SrF e 2−x N i x As 2 superconductor.